Humic acid interaction with clay minerals: modification of the surface properties by calcium presence - Fernández Solarte, Alejandra María (2015)
The environmental importance of humic acid (HA) is mainly related to soil fertility, but it can also develop some human diseases by its intake as well as prevent calcium assimilation. Physicochemical characterisations of a montmorillonite (Mt) and its thermal treated product (Mt550), to which HA, Ca+2 or both were added, will help to better understand the surface behaviour of the binary or ternary systems. Calcium or HA adsorption produces a decrease of the Mt and Mt550 specific surface area (SSA). X-ray diffraction indicates calcium presence and no entrance of humic acid in the interlayer of Mt, while in the ternary systems (calcium-HA-Mt) a hindrance to the calcium entrance was observed. The opposite behaviour produces the adsorption of HA or calcium on electric charge of both samples. The mean pore diameter (MPD) for Mt increases with Ca+2 adsorption while no change was found after HA adsorption, in contrast to that found for Mt550.